2016
DOI: 10.2298/csis151207065v
|View full text |Cite
|
Sign up to set email alerts
|

Aspects and roles in software modeling: A composition based comparison

Abstract: It's intriguing how the work on inherent aspect-oriented modeling almost completely ignores the similarity between aspect-oriented and role based decomposition and composition. Ever since the notion of aspect entered the software development arena, it has been compared to the notion of role. Findings range from identifying greater similarities to more cautious observations that albeit aspects and roles are similar, they appear to be more as complimentary with a significant effort needed to really bring them to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Various authors have worked on the topic of review meetings in context of agile methods. In Vranic and Laslop (2016) and de Gea et al (2015), authors discussed the requirement engineering perspective and have showed the importance of review meetings and discussed various types. The work was focused on the interaction of teams during meetings and the collaboration among team members.…”
Section: Research Findingsmentioning
confidence: 99%
“…Various authors have worked on the topic of review meetings in context of agile methods. In Vranic and Laslop (2016) and de Gea et al (2015), authors discussed the requirement engineering perspective and have showed the importance of review meetings and discussed various types. The work was focused on the interaction of teams during meetings and the collaboration among team members.…”
Section: Research Findingsmentioning
confidence: 99%